2019
DOI: 10.1016/j.jelechem.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of activated screen printed carbon electrodes for hydrogen peroxide and phenol derivatives sensing

Abstract: Screen-printed carbon electrodes (SPCEs) are widely used for the electroanalysis of a plethora of organic and inorganic compounds. These devices offer unique properties to address electroanalytical chemistry challenges and can successfully compete in numerous aspects with conventional carbon-based electrodes. However, heterogeneous kinetics on SPCEs surfaces is comparatively sluggish, which is why the electrochemical activation of inks is sometimes required to improve electron transfer rates and to enhance sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 48 publications
(52 reference statements)
3
21
0
Order By: Relevance
“…Figure 1 shows the linear scan voltammetry (LSV) curves for the H2O2 electro-oxidation at the different modification steps of the biosensor, both in the absence and presence of H2O2, namely: SPCE, aSPCE, PAA-aSPCE, PtNPs-PAA-aSPCE, and the final biosensor GOx-PtNPs-PAA-aSPCE. (Figure 2A,B), which is a similar response to that reported in the literature [26]. After the electrodeposition of PAA, the surface displayed a smooth morphology, which confirmed that the aSPCE was coated by the polymeric film ( Figure 2C).…”
Section: Characterization and Optimization Of The Electrochemical Persupporting
confidence: 87%
“…Figure 1 shows the linear scan voltammetry (LSV) curves for the H2O2 electro-oxidation at the different modification steps of the biosensor, both in the absence and presence of H2O2, namely: SPCE, aSPCE, PAA-aSPCE, PtNPs-PAA-aSPCE, and the final biosensor GOx-PtNPs-PAA-aSPCE. (Figure 2A,B), which is a similar response to that reported in the literature [26]. After the electrodeposition of PAA, the surface displayed a smooth morphology, which confirmed that the aSPCE was coated by the polymeric film ( Figure 2C).…”
Section: Characterization and Optimization Of The Electrochemical Persupporting
confidence: 87%
“…Presence of most active sites on the electrode surface and removal of the oxide coating in previous studies demonstrated the significant increase in electrochemical performance. 41,42 The SPCE was characterized by CV (−0.4 to +0.6 V) in a solution of 0.1 M KCl containing 5 mM K 3 [Fe (CN) 6 ]/K 4 [Fe (CN) 6 ] with scan rates of 0.1 V/s, after the activation process. The deposition time of the FLGMs could considerably affect the size, deposition quantity and extent of the Au microstructures on the SPCE.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced sensitivity is attributed to the removal of non-electroactive components such as resins, solvents, and additives from the carbon ink induced by the pretreatment. This increases the electroactive area at the working electrode surface, which leads to a nanostructured film on the electrode-solution interface comprising graphite and carbon nanoparticles (Carbon Black) [30]. SEM images of flexible SPEs were collected to assess if the morphology of SPEs is unaffected by the electrochemical pretreatment.…”
Section: Resultsmentioning
confidence: 99%